Interactive online survey raises awareness about cornea donation. Issue 1 (4th February 2020) - Tsigkos, Dimitrios; Tzelepi, Anna; Kopsini, Dimitra; Manolakou, Danae; Konistis, Evangelos; Palioura, Sotiria
Abstract : Objective: To assess the impact of a 5 min interactive online survey on raising awareness about cornea donation and willingness to become a donor. Methods: An interactive online questionnaire was used to collect information regarding awareness, perceptions and attitudes towards cornea donation and to educate the participants about the process and value of cornea donation. Willingness to become a cornea donor was assessed at the beginning and the end of the survey. Results: The survey was completed by 1769 Greek residents. Willingness to become a cornea donor increased from 40.5% (n=717) at the beginning of the survey to 55.2% (n=977) by the end of it (p<0.00001). Younger participants, those whose work or studies were unrelated to the medical field, and those with the least knowledge about cornea donation and transplantation were more likely to change their views towards donation by the end of the survey (42.3%, 44.8% and 82.1% increase in willingness to donate, respectively). Major deterrents to donation were lack of information, concerns about the use of the donated corneas and corruption within the medical field. Conclusion: Our 5 min online survey had a significant impact on changing the mentality towards cornea donation in Greece. We live in an online era and incorporation of online tools and applications in awareness campaigns towards cornea and organ donation has become a necessity.